Behavioral outcomes of complete Freund adjuvant–induced inflammatory pain in the rodent hind paw: a systematic review and meta-analysis. Issue 5 (27th May 2022) - Burek, Dominika J.; Massaly, Nicolas; Yoon, Hye Jean; Doering, Michelle; Morón, Jose A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Many analgesics inadequately address the psychiatric comorbidities of chronic and persistent pain, but there is no standard preclinical model of pain-altered behavior to support the development of new therapies. To explore this conflicting and inconclusive literature, we conducted a focused systematic review and meta-analysis on the effect of complete Freund adjuvant–induced (CFA) rodent hind paw inflammation on multiple classical indicators of exploratory behavior, stress coping, and naturalistic behavior. Our primary objective was to define CFA's effect on assays including, but not limited to, the elevated plus maze and forced swim test. Our secondary objective was to discover how variables such as species and strain may influence outcomes in such assays. We searched Ovid MEDLINE, Embase, Scopus, and Web of Science in April and October 2020 for studies with adult rodents injected with CFA into the hind paw and subsequently tested for aspects of "anxiety-like" or "depressive-like" behaviors. Forty-four studies evaluated performance in the elevated plus or zero maze, open field test, light–dark box, place escape and avoidance paradigm, forced swim test, tail suspension test, sucrose preference test, wheel running, and burrowing assay. Complete Freund adjuvant modestly but significantly decreased exploratory behavior, significantly increased passive stress coping in the tail suspension test but not the forced swim test, and significantly decreased preference for sucrose and naturally rewarding activity. Subgroup analyses revealed significant differences between species and animal sourcing. Based on the evidence provided here, we conclude future studies should focus on CFA's effect on natural rewards and naturalistic behaviors.